Penerapan Pasal 59 Undang-Undang Nomor 35 Tahun 2014 Terhadap Anak sebagai Korban Perlakuan Salah dan Penelantaran - Pricilia Uty Vianty Loppies; Elsa Rina Maya Toule; Carolina Tuhumury (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Children are entrusted by God who must be guarded, cared for, and also loved because children are a mandate as well as a gift from God that is one and only one that we must always protect because they are inherent in their dignity and human rights that must be upheld. The law has regulated special protection for children who are victims of abuse and neglect but it has not been effective yet because it has not had a deterrent effect on parents.Purposes of the Research: This study aims to examine and explain the form of law enforcement against child victims of abuse and neglect.Methods of the Research: The research method in this writing uses empirical research, with a descriptive analytical approach, the problem approach used is library research and field studies. The sources of legal materials used are primary legal materials and secondary legal materials. Data collection techniques through unstructured interviews and literature study were then analyzed.Results of the Research: The results showed that the mistreatment and abandonment of children is due to lack of economic factors, attention and awareness of parents so as to make the child dare to sell newspapers, menmen, and pick up scrap metal. Not only that the role of law enforcement officials has not been effective to handle the case so there has been no deterrent effect for parents and children.